2021
DOI: 10.4103/aip.aip_84_20
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis Unmasked by Gaming

Abstract: With easy accessibility and advancements in technology, there has been an upsurge in gaming. Players may neglect their real life, even using gaming as a medium to build self esteem. This has led to increased prevalence of gaming disorder. There is a dearth of literature regarding the interplay between gaming disorder and psychosis. Here, we present three cases where a prodromal history of progressively increasing time spent gaming was found to be followed by the emergence of florid psychotic symptoms. Gaming m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…However, our findings showed that the association between symptoms of hikikomori and total distress due to PLEs did not vary according to PIU, after controlling for the effects of individual vulnerability factors, distress due to PLEs was primarily associated with the psychoticism trait domain of personality and symptoms of anxiety. Despite this, it is possible that the complex association between hikikomori, PIU, and psychotic symptoms became evident during young adulthood and adulthood, in accordance to the reports of clinical cases [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ] and previous studies [ 52 , 56 ]. Thus, longitudinal studies with representative samples of different population are needed.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, our findings showed that the association between symptoms of hikikomori and total distress due to PLEs did not vary according to PIU, after controlling for the effects of individual vulnerability factors, distress due to PLEs was primarily associated with the psychoticism trait domain of personality and symptoms of anxiety. Despite this, it is possible that the complex association between hikikomori, PIU, and psychotic symptoms became evident during young adulthood and adulthood, in accordance to the reports of clinical cases [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ] and previous studies [ 52 , 56 ]. Thus, longitudinal studies with representative samples of different population are needed.…”
Section: Discussionsupporting
confidence: 87%
“…Another important aspect of this study was our test of the hypothesis that PIU may represent a risk factor that moderates the relationship between symptoms of social withdrawal and distress due to PLEs. Several reports [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ] of clinical cases seem to support the explanation in which severe social withdrawal and PIU mutually reinforce each other over time, with a progressive abandonment of social and school or work activities until symptoms of psychosis emerge. However, our findings showed that the association between symptoms of hikikomori and total distress due to PLEs did not vary according to PIU, after controlling for the effects of individual vulnerability factors, distress due to PLEs was primarily associated with the psychoticism trait domain of personality and symptoms of anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A better understanding of the gamer’s motivations of patients who use video games as a coping strategy could lead to targeted interventions to promote positive outcomes [46, 47]. In other cases, presented by Angane et al [48], patients turned to gaming for reality substitution because of the distressing symptoms that they experienced, and progressively increased their gaming time, leading to a GD. These observations also suggest that gaming could be beneficial for patients facing psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few clinical cases involving video game playing and psychotic symptoms have been previously reported in literature. In some cases, the psychosis breakdowns have occurred due to excessive playing, while in others, it has been considered to be a result of withdrawal symptoms of gaming disorder [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%